Hi-JAKi-ng Synovial Fibroblasts in Inflammatory Arthritis With JAK Inhibitors - Burja, Blaž; Mertelj, Tonja; Frank-Bertoncelj, Mojca (Frontiers in Medicine, 2020)
The Janus kinase (JAK)—Signal transducer and activator of transcription (STAT) pathway is one of the central signaling hubs in inflammatory, immune and cancer cells. Inhibiting the JAK-STAT pathway with JAK inhibitors (jakinibs) constitutes an important therapeutic strategy in cancer and chronic inflammatory diseases like rheumatoid arthritis (RA). FDA has approved different jakinibs for the treatment of RA, including tofacitinib, baricitinib and upadacitinib, and several jakinibs are being tested in clinical trials. Here, we reviewed published studies of jakinib effects on resolving synovial pathology in inflammatory arthritis. We discussed the results of jakinibs on structural joint damage in clinical trials and explored the effects of jakinibs across different in vitro, ex vivo, and in vivo synovial experimental models. We delved rigorously into experimental designs of in vitro fibroblast studies, deconvoluted jakinib efficacy in synovial fibroblasts across diverse experimental conditions and discussed their translatability in vivo. Synovial fibroblasts can readily activate the JAK-STAT signaling pathway in response to cytokine stimulation. We highlighted rather limited effects of jakinibs on the in vitro cultured synovial fibroblasts and inferred that direct and indirect (immune cell-dependent) actions of jakinibs are required to curb the fibroblast pathology in vivo. These actions have not been mimicked optimally in current in vitro experimental designs, where inflammatory stimuli do not naturally clear out with treatment as they do in vivo. While summarizing the broad knowledge of synovial jakinib effects, our review uniquely challenges future study designs to mimic better the jakinib actions in broader cell communities, as occurring in vivo in the inflamed synovium. This can deepen our understanding of collective synovial activities of jakinibs and their therapeutic limitations, thereby fostering jakinib development in arthritis.